Some danger involved eaudiobook - Thomas, Will (Barker & Llewelyn, 2016)
An atmospheric debut novel set on the gritty streets of Victorian London, Some Danger Involved introduces detective Cyrus Barker and his assistant, Thomas Llewelyn, as they work to solve the gruesome murder of a young scholar in London's Jewish ghetto. When the eccentric and enigmatic Barker takes the case, he must hire an assistant, and out of all who answer an ad for a position with "some danger involved," he chooses downtrodden Llewelyn, a gutsy young man with a murky past. As they inch ever closer to the shocking truth behind the murder, Llewelyn is drawn deeper and deeper into Barker's peculiar world of vigilante detective work, as well as the heart of London's teeming underworld. Brimming with wit and unforgettable characters and steeped in authentic period detail, Some Danger Involved is a captivating novel that introduces an equally captivating duo.